Komunikasi Budaya Musik Tanah Liat Komunitas JAF - Ade Ahmad Sujai; Yusuf Sapari; Muhammad Kamaluddin (JIKE: Jurnal Ilmu Komunikasi Efek, 2018)
Abstract This research describes the cultural communication of Jatiwangi Art Factory (JAF) Community. Through the use of clay-based musical instruments, JAF communicates the identity of the Jatiwangi community in the form of precariousness to the wider audience. Not only to the Sundanese community where Jatiwangi culture grows and develops, but also to all people with various cultural backgrounds in Indonesia and even the world. The method used in this research is qualitative method with ethnography approach. The data were obtained by direct research involvement in JAF community located in Jatiwangi Sub-district, Majalengka Regency, West Java Province. The results showed that cultural communications conducted JAF is through the primary and secondary processes. The primary process in question is through direct communication in the form of face-to-face and socialization to the general public outside Jatiwangi. The second mentioned is a secondary process through the use of communication media in the form of concerts and music festivals. Concerts and festivals are conducted around the region in Indonesia and even the world. In such a way that what was done earlier confirmed the cultural identity of Jatiwangi community to other community of cultural stakeholders. Identity that shows as a community of stakeholders of clay culture (rooftile) and its accompanying matters. Keywords : communication, cultural, identity,Sundanese, JAF.